Disaster Risk Management and Quality of Life in Vulnerable Areas in Lima, Peru - Torcello-Pereyra, Nora Yocelin; Ríos-Lama, Cristian Armando; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
Natural disasters always pose a threat to residents living in vulnerable areas, and only proper disaster risk management can bring peace of mind and improve the quality of life for potential victims. Therefore, this study aims to determine the existence of a relationship between disaster risk management and the quality of life in vulnerable areas of the San Miguel District, Lima, in 2023. This non-experimental, cross-sectional, and correlational descriptive study selected a sample of 95 residents from vulnerable areas using a non-probabilistic method. Questionnaires were employed as measurement instruments, and surveys served as the data collection technique. It was statistically determined that there is a weak but significant positive relationship between disaster risk management and quality of life, with a coefficient of Rho = 0.311 and Sig. = 0.002. Thus, it can be asserted that, in the studied sample, if disaster risk management is high, the quality of life for residents in vulnerable areas of the San Miguel District, Lima, in 2023, will also be in good conditions.